Subthalamic nucleus stimulation induces deficits in decoding emotional facial expressions in Parkinson's disease. Issue 2 (23rd January 2004) - Dujardin, K; Blairy, S; Defebvre, L; Krystkowiak, P; Hess, U; Blond, S; Destée, A
Abstract : Background: Bilateral subthalamic nucleus (STN) stimulation is recognised as a treatment for parkinsonian patients with severe levodopa related motor complications. Although adverse effects are infrequent, some behavioural disturbances have been reported. Objective: To investigate the consequences of STN stimulation on emotional information processing in Parkinson's disease by assessing the performance of an emotional facial expression (EFE) decoding task in a group of patients before and after surgery. Methods: 12 non-demented patients with Parkinson's disease were studied. They were assessed one month before surgery and three months after. Their ability to decode EFEs was assessed using a standardised quantitative task. Overall cognitive function, executive function, visuospatial perception, depression, and anxiety were also measured. Twelve healthy controls were matched for age, sex, and duration of education. Results: Before surgery, the patients showed no impairment in EFE decoding compared with the controls. Their overall cognitive status was preserved but they had a moderate dysexecutive syndrome. Three months after surgery, they had significant impairment of EFE decoding. This was not related to their overall cognitive status or to depression/anxiety scores. Visuospatial perception was not impaired. There was no change in the extent of the dysexecutive syndrome except for a reduction in phonemic word fluency. Conclusions: Bilateral STN stimulation disturbs negative emotional information processing in Parkinson's disease. The impairment appears specific and unrelated to certain secondary variables. This behavioural complication of STN may have implications for the patient's social life.